Zingiber officinale Protective Effects on Gentamicin's Toxicity on Sperm in Rats - A Zahedi; A Khaki; HR Ahmadi-Ashtiani; H Rastegar; Sh Rezazadeh (Institue of Medicinal Plants, ACECR, 2010)
Background: Ginger rhizome (Zingiber officinale R., family: Zingiberaceae) is used medicinally and as a culinary spice and has anti-oxidant and cell-protective effects in animals and humans body. Objective: The aim of this study was to investigate the influence of Ginger rhizome toxicity of Gentamicin on sperm parameters in male rats. Methods: Forty Wistar male rat (n=40) were allocated into four groups, control (n=10) and test groups (n=30), that subdivided into groups of 3 that received ginger rhizome powder (100 mg/kg/day), gentamicin group that received, 5 mg/kg/day and ginger group that received, 5 mg/kg/day gentamicin additionally, for 30 consequence day. Animals were kept in standard conditions. In thirty day the testes tissue of Rats in whole groups were collected. Results: Ginger administration caused a marked increase in the testosterone concentrations of the rats even in spite of receiving 5 mg/kg/day gentamicin in compared with the control and gentamicin treated groups. Conclusion: Ginger rhizome is able to overcome reproductive toxicity of gentamicin and induces spermatogenesis probably mainly through the elevation of testosterone levels.